Release from sheep‐grazing appears to put some heart back into upland vegetation: A comparison of nutritional properties of plant species in long‐term grazing experiments. (27th April 2020) - Marrs, Robert H.; Lee, HyoHyeMi; Blackbird, Sabena; Connor, Leslie; Girdwood, Susan E.; O'Connor, Michael; Smart, Simon M.; Rose, Robert J.; O'Reilly, John; Chiverrell, Richard C.
Abstract: Rewilding or wilding is a popularised means for enhancing the conservation value of marginal land. In the British uplands, it will involve a reduction, or complete removal, of livestock grazing (sheep), based on the belief that grazing has reduced plant species diversity, the 'Wet Desert' hypothesis. The hope is that if livestock is removed, diversity will recover. If true, we hypothesise that the species extirpated/reduced by grazing and then recover on its removal would more nutritious compared to those that persisted. We test this hypothesis at Moor House National Nature Reserve (North‐Pennines), where seven sets of paired plots were established between 1953 and 1967 to compare ungrazed/sheep‐grazed vegetation. Within these plot‐pairs, we compared leaf properties of seven focal species that occurred only, or were present in much greater abundance, in the absence of grazing to those of 10 common species that were common in both grazed and ungrazed vegetation. Each sample was analysed for macro‐nutrients, micro‐nutrients, digestibility, palatability and decomposability. We ranked the species with respect to 22 variables based on effect size derived from Generalised Linear Modelling (GLM) and compared species using a Principal Components Analysis. We also assessed changes in abundance of the focal species through time using GLMs. Our results support the 'Wet Desert' hypothesis, that is, that long‐term sheep grazing has selectively removed/reduced species like our focal ones and on recovery, they were more nutritious (macro‐nutrients, some micro‐nutrients) palatable, digestible and decomposable than common species. Measured changes in abundance of the focal species suggest that their recovery will take 10–20 years in blanket bog and 60 years in high‐altitude grasslands. Collectively, these results suggest that sheep grazing has brought about biotic homogenization, and its removal in (re)wilding schemes will reverse this process eventually! The 'white woolly maggots' have eaten at least part of the heart out of the highlands/uplands, and it will take some time for recovery. Abstract :